Stopping Smokeless Tobacco Use: A Call to Action - Reed, Donald; Bowen, Elaine; Fint-Clark, Becca; Clark, Brent; Cobb, Nila; Danberry, Kathy M.; Hutson, Zona; Lusk, Stephanie; Rine, Jason; Robinson, Natasha (Frontiers in Public Health, 2021)
In the United States, single smokeless tobacco use continues to increase in conjunction with the dual use of smokeless tobacco and other nicotine products. Problematically, much of the tobacco prevention literature and funding inundates tobacco users with smoking tobacco information while neglecting to provide them any information about smokeless tobacco. Meanwhile, American tobacco companies continually market new and dissolvable tobacco products targeted at non-smokers. New data suggests that smokeless tobacco use is, also, increasing in West Virginia and, in order to address this increased use, the West Virginia Extension Service recently partnered with the Division of Tobacco Prevention in the West Virginia Department of Health and Human Resources to develop a comprehensive spit tobacco curriculum for West Virginia students between third and sixth grade. This article details the development and assessment of the spit tobacco prevention curriculum and the resulting report from the initial pilot of the program. The curriculum was piloted across six counties with the participation of schools, after-school programs and 4-H clubs. After implementation, survey results demonstrate that youth have increased awareness of the health effects of smokeless tobacco. Throughout the article, we explore West Virginia's Cooperative Extension Service's response to this emerging public health issue and release a call to action for the National Cooperative Extension Services to join us in spit tobacco prevention.